How coaches influence referee decisions - Negri, M. (2015)
This work focuses on the influence of coaches on referees' decisions. Even though this topic is not new in sports science, the present study contributes to the closing of a scientific gap by its specific application to non-professional soccer. This aim is reached by consulting the principal- agent theory as the foundation. In a first step, a scientific gap in research on the factors influencing referees' decisions is identified with special regard to a setting in non-professional soccer. Following, the structures and specificities of refereeing in amateur soccer are presented before introducing the principal- agent theory as the major theoretical pillar of this study. Subsequent to the presentation of the theory, its appropriateness for a transfer to the relation between referee boards (principal) and referees (agent) to non-professional soccer is evaluated. This is done against the specific background of a coach entering this dyad as a third party with a 'principal-like' role. It is elaborated that the basic contemplation of the principal-agent theory can also be found in the presented setting. In this context, the solution mechanisms proposed by the principal-agent theory are evaluated with respect to their applicability in a sports-related setting. The outcome is that the most promising approach to reduce problems is to foster intrinsic motivation, whereas other solution mechanisms can neither be realized nor seem promising in the specific setting. After having set the framework of the empirical study, the working model is presented. It aims at investigating if and how a third party (coach) can influence the performance of an agent (referee) who actually performs on behalf of another principal (the referee board). In this respect, the scope is dedicated to the agent's discretionary power as it represents a significant, yet non-verifiable impact on the outcome of the agent's performance. The underlying questions for this study are developed based upon this working model. Those are aimed at figuring out if and how a third party can influence an agent even though it does not possess the formal right to do so. Subsequently, the methodology of this study is presented. Two pillars form the basis of the research project. First of all, separate questionnaires for coaches and referees are developed with the aim of learning more about their mutual relation and behavior with respect to influencing attempts. Second of all, the results of both questionnaires are evaluated against the background of official match data. This objective means shall help to find out if influencing is taking place and if it finds measurable expression in matches (e.g., the result or personal sanctions). The focus of interest is set on verbal strategies. It is found out that the third party shows a tendency to influence the agent for his own benefit. The third party can be successful in doing so, but does not necessarily face an advantageous treatment as a consequence. Additionally, not all verbal strategies show a significant result. Even in cases in which a significant influence is detected, the extent of influences is weak. The success or failure of verbal influences is moderated by the agent's reaction (discrimination) in some cases. It is of particular interest that one has to pay attention to the kind of combination between the strategy chosen by the coach and the respective reaction of the agent. In some cases, the strategy is the decisive factor for a significant influence; in others it is the agent's reaction, or the combination of both. A general proposition with respect to the effectiveness of influencing strategies can therefore not be made. Instead, the success or failure depends on the specific constellation between the strategy and the referee's reaction. Taking the findings from the empirical analysis into account, recommendations for an adaptation of single elements of the principal-agent theory are made. It is found that the pure economic view of the basic theory neglects that humans do not always act in a perfect economic sense. Rather, their decisions are based on past experiences or emotions. In its postulation of integrating a psychological view of the theory, this study supports other works criticizing the theory for its rather limited view on human behavior. In contrast to the theory, this study identifies a different image of the agent. The reason for that is that he is not necessarily egoistic and profit maximizing, but may also be a trustful principal's cooperator. Following this view, poor performance may also not only be the result of the agent's missing willingness to perform well, but rather a consequence of insufficient abilities. Aforementioned results have been transferred to the daily challenges of a manager (principal) who assigns an employee (agent) to a joint project in the company. In this constellation, the manager also needs to secure that the employee acts in his own best interest without being distracted by other project collaborators. Holistic recommendations for solutions do not seem to be applicable in this kind of setting. The most feasible measure could be to get to know the employee in order to reduce existing information asymmetries. Based upon this consideration, the manager might figure out how to properly motivate the employee and make him concentrate on the original tasks. It is recommended that future research on this topic may be done in other non-professional sports. In contrast to professional leagues, the circumstances in amateur sports differ significantly and allow for further interesting insights into principal-agent relationships. The presented setting may be the starting point for further research. Especially the existing (and constantly growing) database with match data may be used for related studies, such as a comparison with other sports elaborating similarities and differences. Additionally, the growing database might allow for the identification of tendencies over several years. Considering the fact that the coach strategy and the referee reaction explain less than 10% of total variance, this limitation is also linked to the recommendation of elaborating on further aspects influencing match results in non-professional soccer in future studies. ABSTRACT FROM AUTHOR